An insight on survey questionnaire design for Green SCM: Using cognitive interviewing method - Savita, K.S. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper features cognitive interviewing method adopted in the pre-test study along with operational definition of the research variables adapted in the study. The findings from cognitive interviews contributed as part of the psychometric testing in improving the survey questionnaire design and content. The cognitive interviews were conducted with five managers from ISO 14001 manufacturing firms in Malaysia. These firms are selected based on purposive sampling method since the ISO 14001 certified firms are in the best position to provide the required information since the adoption and implementation of green practices in their operations are expected. The evidences showed that some participants face difficulty the grasping certain terminology and phase, therefore the interpretation of the questions may vary. Whilst, others face difficulty to comprehend, retrieve and response to the items since the coverage of the content are broad in nature as it focuses on supply chains, information technologies and systems as well as performance. In addition, the participants provide value feedback on the content, format of questionnaire, language, instructions, length as well as response options and scale. The identified issues were clarified and revised in producing the enhanced survey questionnaire for actual data gathering among ISO14001 Manufacturing firms in Malaysia. Â© 2016 IEEE.